Climate Impacts on Energy Systems : Key Issues for Energy Sector Adaptation - Ebinger, Jane; Vergara, Walter (World Bank, 2012)
This report presents an overview of how the energy sector might be impacted by climate change and what options exist for its management. It focuses on energy sector adaptation, rather than mitigation, which has been a key focus of the energy sector and is not discussed in this report. This report draws on available scientific and peer-reviewed literature in the public domain and takes the perspective of the developing world to the extent possible. It starts with a discussion about observed and projected climate change (out to 2100), exploring trends, extremes, and 'hotspots'- geographic regions that will see significant changes or variability for relevant parameters (for example, temperature, runoff , and sea level rise). It then discusses what is known about the impacts of these changes on energy resources, infrastructure, and transportation systems as well as demand. It discusses what technologies or services are more vulnerable and identifies gaps in information or knowledge. The report concludes with a number of proposed near-term actions to foster dialogue, to further inform sector practitioners, to disaggregate climate impacts to regional and local settings, and to improve the knowledge base. Underpinning all actions is recognition of the need for a broad and participatory approach that extends beyond traditional planning horizons and boundaries.